2020
DOI: 10.1016/j.eururo.2020.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine and Smart Working: Recommendations of the European Association of Urology

Abstract: Context: Telemedicine provides remote clinical support using technological tools. It may facilitate health care delivery while reducing unnecessary visits to the clinic. The coronavirus disease 2019 (COVID-19) outbreak has caused an abrupt change in our daily urological practice, converting many of us to be reliant on telehealth. Objective: To provide practical recommendations for effective use of technological tools in telemedicine. Evidence acquisition: A Medline-based and gray literature search was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 24 publications
(35 reference statements)
1
57
0
2
Order By: Relevance
“…Our study reported the data of more than 600 phone counselling for urological benign pathology: notwithstanding the simple call may seem an obsolete approach for telemedicine and may even seem inadequate for clinical visits, it perfectly matches the recommendations of the European Association of Urology [8]. In fact, the phone call, performed by using hospital phones, can be considered the rst and easiest approach for telemedicine, as reported in previously published experiences, for the management of prostate cancer [11], hematuria [12], stones [13,14], urinary incontinence [15,16] and urinary tract infections [17].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Our study reported the data of more than 600 phone counselling for urological benign pathology: notwithstanding the simple call may seem an obsolete approach for telemedicine and may even seem inadequate for clinical visits, it perfectly matches the recommendations of the European Association of Urology [8]. In fact, the phone call, performed by using hospital phones, can be considered the rst and easiest approach for telemedicine, as reported in previously published experiences, for the management of prostate cancer [11], hematuria [12], stones [13,14], urinary incontinence [15,16] and urinary tract infections [17].…”
Section: Discussionsupporting
confidence: 56%
“…In order to ll the blank of o cial guidelines concerning the correct execution of a telemedicine counseling, Socarrás et al [8] outlined its main principles and characteristics, highlighting some crucial aspects such the maintenance of professionalism, privacy, con dentiality whilst reaching satisfying levels of data transmission and comprehension.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, health care systems aggressively pushed for increased usage of telemedicine, with institutions such as New York University increasing their telemedicine use by over 4000% during this time [ 8 ]. The increase in telemedicine has inspired several organizations, including the European Association of Urology, to create recommendations for its professional usage, and some subspecialties have even provided guidelines for treating specific conditions via telemedicine [ 9 , 10 ]. The major shift in health care brought on by the COVID-19 pandemic has also seemingly incentivized all health care practices to more readily adopt telemedicine in their practices.…”
Section: Introductionmentioning
confidence: 99%
“…Our study reported the data of more than 600 phone counselling for urological benign pathology: notwithstanding the simple call may seem an obsolete approach for telemedicine and may even seem inadequate for clinical visits, it perfectly matches the recommendations of the European Association of Urology [ 10 ]. In fact, the phone call, performed using hospital phones, can be considered the first and easiest approach for telemedicine, as reported in previously published experiences, for the management of prostate cancer [ 11 ], hematuria [ 12 ], stones [ 13 , 14 ], urinary incontinence [ 15 , 16 ] and urinary tract infections [ 17 ].…”
Section: Discussionmentioning
confidence: 84%
“…To fill the blank of official guidelines concerning the correct execution of a telemedicine counseling, Rodriguez Socarrás et al [ 10 ] outlined its main principles and characteristics, highlighting some crucial aspects such the maintenance of professionalism, privacy, confidentiality whilst reaching satisfying levels of data transmission and comprehension.…”
Section: Discussionmentioning
confidence: 99%